ERRATUM TO: THE INFLUENCE OF SILICA CALCINATION TEMPERATURE VARIATION TO THE HYDROPHOBICITY AND TRANSMITTANCE ON GLASS SUBSTRATE - Rohmah, Roihatur; Zainuri, Mochamad (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Erratum: Roihatur Rohmah, M. Zainuri. Jurnal Neutrino:Jurnal Fisika dan Aplikasinya. 2020 April: 12(2):49-56. (Doi: 10.18860/neu.v12i2.8208: The title "The Influence of Silica Calcination Temperature Variation to The Hydrophobicity and Transmittance on Glass Substrate" was deleted because it is the same as the author's thesis.Therefore, the title was replaced with "Study of Hydrophobic Surface by Silica Calcination Temperature Variation."